Antioxidant Properties of ADJ6 and ITS Effect on Isolated Human Erythrocyte Ghost Membrane - Duraiswamy, Anand; Shanmugasundaram, Devanand; Sheela Sasikumar, Changam; M. Cherian, Sanjay; Mammen Cherian, Kotturathu (Free Radicals and Antioxidants)
Introduction: Oxidative stress is one of the major causes for many adverse complications especially in disorders such as diabetes, cardiovascular diseases, cancer, etc. Many studies have proven that erythrocytes are affected during these conditions and oxidative stress plays a critical role in damaging the membrane integrity of erythrocytes by inducing lipid peroxidation causing instability to membrane in turn affecting the ion transport mechanisms. Objective and methods: The present study focuses to study the ameliorative effect of ADJ6 against oxidative stress on human erythrocytes. The membrane stabilization activity, Inhibition of lipid peroxidation and the effect against Ouabain induced Na+ K+ ATPase activity was assessed. Further, in vitro antioxidant activity of ADJ6 was also determined. Results and Discussion: DPPH radical scavenging activity, metal chelating and H2 O2 radical scavenging activity were IC50=37.9 ± 0.22 µg/ml, IC50=53.95 ± 0.337 µg/ml and IC50=69.5 ± 0.628 µg/ml respectively. ADJ6 showed an EC50=90.83 ± 1.905 µg/ml against hypotonicity induced lysis of erythrocytes. H2 O2 induced Lipid peroxidation of ghost membrane was also inhibited by ADJ6 (IC50=84.5 ± 2.613 µg/ml). Ouabain induced sodium potassium ATPase activity increased with the treatment of ADJ6 in a dose dependent manner. This proves that ADJ6 is effective in stabilizing the membrane potential of erythrocyte membrane. The scavenging activity in vitro also proves that ADJ6 is effective against free radicals. Conclusion: Though exact mechanism hitherto unknown, it is evident that ADJ6 stabilizes erythrocyte membrane activity. Further studies will be conducted in order to prove the mechanism of action of ADJ6 against of free radicals.
Keywords: Polyherbal formulation; ADJ6; Antioxidant; Erythrocyte ghost membrane; Na+ K+ ATPase